Multisensory Preclinical Training Strategy of Periodontal Scaling for Undergraduates - Xin Huang; Linhesheng Wei; Yang Ning; Zhengmei Lin; Yun Hong (Elsevier, 2023)
Background: Invisibility of subgingival scaling is the most important negative factor affecting the performance of periodontal treatment. A multisensory teaching strategy is used in the preclinical training of undergraduates in order to increase the haptic-auditory-visual feedback, aiming to overcome the invisibility and achieve minimal postoperative complications, improving patients' treatment experience. Methods: One hundred undergraduate dental students in grade 5 were divided into a multisensory teaching strategy group (MTS: n = 50) and a conventional training pattern group (CTP: n = 50). All participants attended a lecture on using an ultrasonic subgingival scaler (USS) and Gracey curettes (GRA), followed by a 3-week training programme. Students in the MTS group were trained in a haptic/auditory-visual feedback manner, whereas students in the CTP group were trained conventionally. After the training phase, paired students in the 2 different groups performed subgingival scaling in paired patients with equivalent teeth of periodontitis using USS and GRA. Objective and subjective postoperative evaluations were recorded. Probing depth (PD) and gingival index (GI) were evaluated before and 4 weeks after scaling by the same periodontal specialist. Results: MTS significantly reduced treatment time and ameliorated postoperative complications (gingival injury, haemorrhage and root surface roughness; P < .05). Postoperative sensitivity was reduced in the MTS group from day 1 to day 7 (D1-D5: P < .001; D6: P = .002; D7: P = .003), whereas postoperative pain was reduced on day 1 (P = .006), compared with that in the CTP group. The PD reduction was not significant between the groups (MTS: 3.17 ± 0.95 mm vs CTP: 3.07 ± 0.97 mm, P > .05), whereas the GI change showed a significant difference between the groups (MTS: 1.71 ± 0.41 vs CTP: 1.67 ± 0.41, P < .05). Conclusions: Multisensory teaching strategies in the preclinical periodontal training of undergraduates can reduce postoperative complications (gingival injury, postoperative haemorrhage, and root surface roughness) and provide a better treatment experience (decreased treatment time and postoperative pain and sensitivity) for patients.